2022
DOI: 10.5603/cj.a2020.0146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of myocardial infarction with non-obstructive coronary arteries: A prospective single-center study

Abstract: Background: A definition of myocardial infarction with non-obstructive coronary arteries (MINOCA) was published by European Society of Cardiology in 2016. The aim of this study is to analyze the clinical profile and prognosis of these patients in a prospective single-center study and compare it with the literature data. Methods: During a 3-year period, information from every consecutive MINOCA patient was gathered (n = 109). It was then compared with 412 contemporaneous patients with myocardial infarction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
1
12
2
2
Order By: Relevance
“…The prognosis in MINOCA compared to MICAD remains controversial. Although earlier studies suggested a better prognosis of MINOCA as compared to MI with obstructive coronary artery disease (44,45) more recent studies showed no differences in prognosis among MINOCA and patients with MICAD (46)(47)(48). In this study, two patients with MICAD suffered myocardial infarction during the follow-up period.…”
Section: Myocardial Blood Flow In Acute Coronary Syndromecontrasting
confidence: 54%
“…The prognosis in MINOCA compared to MICAD remains controversial. Although earlier studies suggested a better prognosis of MINOCA as compared to MI with obstructive coronary artery disease (44,45) more recent studies showed no differences in prognosis among MINOCA and patients with MICAD (46)(47)(48). In this study, two patients with MICAD suffered myocardial infarction during the follow-up period.…”
Section: Myocardial Blood Flow In Acute Coronary Syndromecontrasting
confidence: 54%
“…Кроме того, для пациентов с ИМБОКА наличие хронического воспаления было показано ранее [4,6]. При этом очагами воспаления у пациентов с ИМБОКА могут являться как нестенозирующие атеросклеротические бляшки, так и дисфункциональное микрососудистое русло [4][5][6]. Так, было выявлено повышение концентрации СРБ, снижение резерва коронарного кровотока и взаимосвязь с хроническим воспалением у пациентов со стабильной стенокардией без стенозирующего атеросклероза [29].…”
Section: Discussionunclassified
“…Наличие микрососудистой дисфункции не исключалось у пациентов ИМБОКА с повышенными провоспалительными цитокинами через 3 мес. от индексного события и обсуждалось в позиционном документе по коронарной микрососудистой дисфункции [5,30].…”
Section: Discussionunclassified
“…Moreover, a recent observational study reported that the number of pro-inflammatory conditions—i.e., autoimmune disorders, connective tissue diseases, active cancer, and infections—was significantly higher in the MINOCA group. Nonetheless, neither all-cause mortality nor hospitalisations for cardiovascular causes differed between the groups at follow-up ( 31 ). At present, the role of inflammatory and autoimmune diseases in the development of SCAD remains controversial.…”
Section: Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…- Anxiety and depression : although anxiety and depression are rather frequent both in MINOCA and in MI with obstructive CAD, psychosocial disorders are more typical of MINOCA ( 31 , 32 ). In a Taiwanese nationwide population-based study including more than 10,000 patients with non-obstructive CAD, over 38% had a prior anxiety disorder ( 33 ).…”
Section: Risk Factors and Comorbiditiesmentioning
confidence: 99%